2007
DOI: 10.1073/pnas.0611468104
|View full text |Cite
|
Sign up to set email alerts
|

The induced prostaglandin E 2 pathway is a key regulator of the respiratory response to infection and hypoxia in neonates

Abstract: Infection during the neonatal period commonly induces apnea episodes, and the proinflammatory cytokine IL-1␤ may serve as a critical mediator between these events. To determine the mechanism by which IL-1␤ depresses respiration, we examined a prostaglandin E2 (PGE2)-dependent pathway in newborn mice and human neonates. IL-1␤ and transient anoxia rapidly induced brainstem-specific microsomal prostaglandin E synthase-1 (mPGES-1) activity in neonatal mice. Furthermore, IL-1␤ reduced respiratory frequency during h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
128
3
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 51 publications
11
128
3
3
Order By: Relevance
“…In addition, we recently suggested that astrocytes also release PGE2 in response to a hypercapnic challenge (Forsberg et al, 2016). This would in part explain the interaction between chemosensitivity and the inflammatory system observed in several studies (Hofstetter et al, 2007;Siljehav et al, 2012;Siljehav et al, 2014;Forsberg et al, 2016). Moreover, in human neonates, rapid elevation of brainstem PGE2 during infectious events is associated with, and may explain, the initial presenting symptoms of infection, which are apnea, bradycardia, and desaturation (Siljehav et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…In addition, we recently suggested that astrocytes also release PGE2 in response to a hypercapnic challenge (Forsberg et al, 2016). This would in part explain the interaction between chemosensitivity and the inflammatory system observed in several studies (Hofstetter et al, 2007;Siljehav et al, 2012;Siljehav et al, 2014;Forsberg et al, 2016). Moreover, in human neonates, rapid elevation of brainstem PGE2 during infectious events is associated with, and may explain, the initial presenting symptoms of infection, which are apnea, bradycardia, and desaturation (Siljehav et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…PGE 2 -induced sensory nerve activation, as assessed by depolarization of vagus nerves, was found to be EP 3 receptor-mediated (Maher et al, 2009). Apnea in human neonates has been related to increased PGE 2 release and EP 3 -mediated modulation of respiratory neurons in the brainstem (Hofstetter et al, 2007). EP 3 receptors may not only participate in infection (sepsis)-induced apnea (Hofstetter et al, 2007) but also may contribute to mortality caused by infection with Streptococcus pneumoniae, according to EP 3 gene deletion studies ).…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…Apnea in human neonates has been related to increased PGE 2 release and EP 3 -mediated modulation of respiratory neurons in the brainstem (Hofstetter et al, 2007). EP 3 receptors may not only participate in infection (sepsis)-induced apnea (Hofstetter et al, 2007) but also may contribute to mortality caused by infection with Streptococcus pneumoniae, according to EP 3 gene deletion studies ). The EP 3 agonist GR 63799X induced S-phase arrest and inhibited fibroblast growth (Sanchez and Moreno, 2006), which is possibly relevant to fibrotic disease of the lungs and fibrosis in general.…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…To further elucidate the roles of PGE 2 pathway in EAE, we particularly focused on mPGES-1, a key enzyme responsible for PGE 2 production in inflammation (20)(21)(22). In EAE lesions, mPGES-1 was colocalized with F4/80, a marker for macrophages, but not with CD4 (Fig.…”
Section: Mpges-1 Exacerbates Eae Pathology Through Th1 and Th17 Cytokinementioning
confidence: 99%